2006
DOI: 10.1111/j.1365-2702.2006.01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal birth after caesarean section (VBAC): exploring women's perceptions

Abstract: Vaginal birth after caesarean section (VBAC): exploring women's PerceptionsAims and objectives. This study was designed to complement local audit data by examining the lived experience of women who elected to attempt a vaginal birth following a previous caesarean delivery. The study sought to determine whether or not women were able to exercise informed choice and to explore how they made decisions about the method of delivery and how they interpreted their experiences following the birth. Background. The risi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Several qualitative studies have looked at factors that influence a woman's decision to attempt VBAC following one caesarean section . These factors are wide ranging, and can be grouped into three distinct themes.…”
Section: Factors Influencing Women's Decisions On Vbacmentioning
confidence: 99%
“…Several qualitative studies have looked at factors that influence a woman's decision to attempt VBAC following one caesarean section . These factors are wide ranging, and can be grouped into three distinct themes.…”
Section: Factors Influencing Women's Decisions On Vbacmentioning
confidence: 99%
“…While no national data are available, state‐level studies suggest that some women may have difficulty accessing VBAC due to lack of availability at local hospitals . Beyond accessibility, several other factors affect women's decisions to attempt VBAC or not, including: attitudes toward childbirth (including orientation toward natural birth), fear of labor pain, perceptions of safety and risk, practical considerations such as scheduling convenience, expected ease of recovery, and prior birth experiences (eg, pain, unplanned cesarean delivery, bonding with the baby), perceived likelihood of VBAC success, information about the risks and benefits of VBAC, wanting the experience of vaginal birth, and perceptions of clinician attitudes . Prior research documenting these relationships predominantly comes from qualitative studies in countries other than the United States (especially the United Kingdom and Australia), and may have limited relevance to VBAC decision‐making in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,[13][14][15] Major influences for a woman to choose VBAC are a woman's sense of control in the decision-making process, physician encouragement for VBAC and delivery-type outcome advantages, both physical and emotional. 16 Some studies report physician and midwife support for VBAC; 17 others report conflicting evidence. 11 A study of women intent on VBAC found that health provider support was not as important as the support of family and friends.…”
Section: Introductionmentioning
confidence: 99%